2020
DOI: 10.1097/eja.0000000000001321
|View full text |Cite
|
Sign up to set email alerts
|

Urinary neprilysin for early detection of acute kidney injury after cardiac surgery

Abstract: BACKGROUND Acute kidney injury (AKI) predicts adverse outcomes after cardiac surgery. The accuracy of using changes in serum creatinine for diagnosis and grading of AKI is limited in the peri-operative cardiac surgical setting and AKI may be underdiagnosed due to haemodilution from cardiopulmonary bypass priming and the need for intra-operative and postoperative volume resuscitation. OBJECTIVES To determine whether the urinary biomarker neprilysin can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…1G ) experienced a steady increase in urine output accompanied by decreasing urinary excretion of the cell injury marker neprilysin. The decrease in sCr showed a delay of about 5 days compared with urinary neprilysin as marker of tubular cell damage ( Bernardi et al, 2021 ; Knafl et al, 2017 ; Pajenda, Mechtler & Wagner, 2017 ). Peak urinary neprilysin levels were significantly higher in infection-associated AKI ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…1G ) experienced a steady increase in urine output accompanied by decreasing urinary excretion of the cell injury marker neprilysin. The decrease in sCr showed a delay of about 5 days compared with urinary neprilysin as marker of tubular cell damage ( Bernardi et al, 2021 ; Knafl et al, 2017 ; Pajenda, Mechtler & Wagner, 2017 ). Peak urinary neprilysin levels were significantly higher in infection-associated AKI ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the renal cell injury marker neprilysin in urine ( Bernardi et al, 2021 ; Pajenda, Mechtler & Wagner, 2017 ) decreased rapidly after elimination of nephrotoxic substances or restoration of oxygenation. The course of urinary neprilysin showed that excretion of hyperplastic epithelial cells began with a short delay of approximately 2 days when urinary neprilysin had flattened.…”
Section: Discussionmentioning
confidence: 99%
“…In view of adverse prognosis caused by AKI, prompt identi cation of renal function deterioration is urgently required. Urinary biomarkers were shown to be sensitive indices for AKI prediction, [22,23] but they cannot be measured continuously and involve time-consuming assessments. NIRS enables real-time monitoring and may earlier detect AKI.…”
Section: Discussionmentioning
confidence: 99%
“…During kidney injury, neprilysin is shed from the tubular brush edge of the kidney and is excreted, which can be detected in urine. The discriminatory power of neprilysin for detecting POD 1 AKI corresponded to an AUC of 0.77 (95% CI 0.65–0.90) [ 24 ].…”
Section: Definition and Diagnosismentioning
confidence: 99%